MMP-9 affects dural cell composition and granulocyte accumulation during neuroinflammation - Shen, Sheng-Hsiang; Gerwien, Hanna; Burmeister, Miriam; Tsang, Yi-Ling; Lu, I-Na; Börsch, Anna-Lena; Deshpande, Tushar; Sorokin, Lydia; Meyer zu Hörste, Gerd (Frontiers in Immunology, 2025)
IntroductionMatrix metalloproteinases MMP-2 and MMP-9 modulate inflammatory processes at the blood–brain barrier (BBB), but their presence and function in the dura mater remain unclear. We therefore investigated their contribution to immune regulation at this site during neuroinflammation.MethodsWe analyzed dura mater from naïve and experimental autoimmune encephalomyelitis (EAE) mice using immunofluorescence, gelatin zymography, flow cytometry, and single-nucleus RNA sequencing (snRNA-seq). Comparisons were performed between wild-type (WT) and Mmp9-/- mice to define gelatinase expression, cellular sources, transcriptional alterations, and immune cell dynamics.ResultsPro- and activated-MMP-2 and MMP-9 were detectable in naïve dura, with selective upregulation of MMP-9 during EAE. Mmp9-/- mice demonstrated delayed EAE onset but more severe disease at peak. SnRNA-seq revealed that Mmp9 deficiency altered endothelial transcriptional programs, especially in venous endothelial cells, and promoted expansion of granulocyte populations with mature neutrophil signatures. Flow cytometry and immunofluorescence confirmed increased Ly6C⁺Ly6G⁺ neutrophils in Mmp9-/- dura during EAE.DiscussionOur findings indicate that MMP-9 regulates immune cell composition and activation within the dura during neuroinflammation. While Mmp9 deficiency delays disease onset, it enhances neutrophil accumulation and inflammatory responses at this CNS border, suggesting a previously unrecognized, potentially anti-inflammatory role for MMP-9 in the dura.